DYRK1A signalling synchronizes the mitochondrial import pathways for metabolic rewiring - Marada, Adinarayana; Walter, Corvin; Suhm, Tamara; Shankar, Sahana; Nandy, Arpita; Brummer, Tilman; Dhaouadi, Ines; Vögtle, Friederike-Nora; Meisinger, Christof (Nature Communications, 2024)
Mitochondria require an extensive proteome to maintain a variety of metabolic reactions, and changes in cellular demand depend on rapid adaptation of the mitochondrial protein composition. The TOM complex, the organellar entry gate for mitochondrial precursors in the outer membrane, is a target for cytosolic kinases to modulate protein influx. DYRK1A phosphorylation of the carrier import receptor TOM70 at Ser91 enables its efficient docking and thus transfer of precursor proteins to the TOM complex. Here, we probe TOM70 phosphorylation in molecular detail and find that TOM70 is not a CK2 target nor import receptor for MIC19 as previously suggested. Instead, we identify TOM20 as a MIC19 import receptor and show off-target inhibition of the DYRK1A-TOM70 axis with the clinically used CK2 inhibitor CX4945 which activates TOM20-dependent import pathways. Taken together, modulation of DYRK1A signalling adapts the central mitochondrial protein entry gate via synchronization of TOM70- and TOM20-dependent import pathways for metabolic rewiring. Thus, DYRK1A emerges as a cytosolic surveillance kinase to regulate and fine-tune mitochondrial protein biogenesis.
Gesehen am 17.01.2025